The investment checklist : the art of in-depth research - Shearn, Michael, 1975- (Hoboken, NJ : Wiley, 2011)
'A practical guide to making more informed investment decisionsInvestors often buy or sell stocks too quickly. When you base your purchase decisions on isolated facts and don't take the time to thoroughly understand the businesses you are buying, stock-price swings and third-party opinion can lead to costly investment mistakes. Your decision making at this point becomes dangerous because it is dominated by emotions. The Investment Checklist has been designed to help you develop an in-depth research process, from generating and researching investment ideas to assessing the quality of a business and its management team. The purpose of The Investment Checklist is to help you implement a principled investing strategy through a series of checklists. In it, a thorough and comprehensive research process is made simpler through the use of straightforward checklists that will allow you to identify quality investment opportunities. Each chapter contains detailed demonstrations of how and where to find the information necessary to answer fundamental questions about investment opportunities. Real-world examples of how investment managers and CEOs apply these universal principles are also included and help bring the concepts to life. These checklists will help you consider a fuller range of possibilities in your investment strategy, enhance your ability to value your investments by giving you a holistic view of the business and each of its moving parts, identify the risks you are taking, and much more.Offers valuable insights into one of the most important aspects of successful investing, in-depth researchWritten in an accessible style that allows aspiring investors to easily understand and apply the concepts coveredDiscusses how to think through your investment decisions more carefullyWith The Investment Checklist, you'll quickly be able to ascertain how well you understand your investments by the questions you are able to answer, or not answer, without making the costly mistakes that usually hinder other investors'--
Includes index.
Keywords: Investment analysis; Portfolio management; Investments